“God’s Grandeur” by Gerard Manley Hopkins. A Poetic Path into the Depths of Contemplation - Marcin Godawa (Polonia Sacra)
The present paper concerns the question of how Christian contemplation, in the sense of a simple loving gaze on God and His works, could be prepared and supported by poetry by using the properties of poetic speech in the field of semantics, syntax as well as sound effects. The object is God’s Grandeur, a brilliant sonnet by Gerard Manley Hopkins, a poet, priest, Jesuit, a man of spiritual passion. Its analysis along with interpretation, in terms of both poetics and spiritual theology, will allow us to see how aesthetic contemplation works and could bear fruit for a contemporary man’s relation to himself or herself, to the world as well as most importantly to God, the source of created goodness.